2011
DOI: 10.1007/s11064-011-0674-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain Serum Amyloid P Levels are Reduced in Individuals that Lack Dementia While Having Alzheimer’s Disease Neuropathology

Abstract: The neuropathological signs of Alzheimer’s disease (AD) include beta amyloid plaques and neurofibrillary tangles. There is a significant population of individuals that have these key hallmarks but show no signs of cognitive impairment, termed non-demented with AD neuropathology (NDAN). The protective mechanism allowing these individuals to escape dementia is unknown. Serum amyloid P (SAP) is a serum protein associated with wound repair that is elevated in the brains of Alzheimer’s patients and binds to amyloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…However, inhibition of SAPC, cathepsin B, or both proteins from HIV-infected MCM before addition to neurons was neuroprotective. Previous reports indicated that SAPC possess neurotoxic properties [31], including the stabilization of amyloid fibrils, which is the hallmark of AD neurodegenerative process [30]. These results suggest that HIV-1 infection is promoting the association of SAPC with cathepsin B more than a change in SAPC expression and/or secretion to increase neurotoxicity.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, inhibition of SAPC, cathepsin B, or both proteins from HIV-infected MCM before addition to neurons was neuroprotective. Previous reports indicated that SAPC possess neurotoxic properties [31], including the stabilization of amyloid fibrils, which is the hallmark of AD neurodegenerative process [30]. These results suggest that HIV-1 infection is promoting the association of SAPC with cathepsin B more than a change in SAPC expression and/or secretion to increase neurotoxicity.…”
Section: Discussionmentioning
confidence: 77%
“…SAPC is involved in acute phase response and is linked to amyloid plaque accumulation by stabilizing amyloid fibrils, thus preventing their degradation [28,29]. It is present in AD patients [30], and induced neuronal apoptosis when injected into rat hippocampus [31]. There is proof of efflux of SAPC at the blood brain barrier (BBB) [32], and accumulation of SAPC in the brain of rats with permeabilized BBB, demonstrating its role in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis from a preliminary study shows strong upregulation of SAP in capillary cerebral amyloid angiopathy [48], and this fi nding is supported by immunochemistry indicating signifi cantly more SAP deposits in microvascular Aβ deposits [23,49]. Previous studies suggested that SAP content of the AD brain can be originated from local synthesis in CNS [24,32] or SAP synthesized by the liver can be transported through BBB by an unknown mechanism [21]. Our in vitro studies on the brain endothelial monolayers demonstrated that SAP can cross BBB in both directions.…”
Section: Discussionmentioning
confidence: 91%
“…The excess of secreted SAP is precipitated in amyloid deposits resulted by different chronic infl ammatory processes [31]. SAP is also synthesized in brain, and increased mRNA and protein levels were detected in brain of AD patients compared to controls [17,24,32]. However, no signifi cant increase in SAP production could be detected in postmortem samples from hippocampus and frontal cortex of nondemented subjects with AD neuropathology [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation